2013
DOI: 10.1038/nrc3484
|View full text |Cite
|
Sign up to set email alerts
|

The effects of PEDF on cancer biology: mechanisms of action and therapeutic potential

Abstract: The potent actions of pigment epithelium-derived factor (PEDF) on tumour-associated cells, and its extracellular localization and secretion, stimulated research on this multifunctional serpin. Such studies have identified several PEDF receptors and downstream signalling pathways. Known cellular PEDF responses have expanded from the initial discovery that PEDF induces retinoblastoma cell differentiation to its anti-angiogenic, antitumorigenic and antimetastatic properties. Although the diversity of PEDF activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
192
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(206 citation statements)
references
References 166 publications
(167 reference statements)
1
192
1
Order By: Relevance
“…Several studies showed that PEDF level declines with age, and suggested that this decline may play a key role in the development of angiogenic-related pathologies (18). Moreover, it was shown that decrease in PEDF expression is one of the mechanisms that promote tumor growth (19), suggesting PEDF as an anticancer therapy (20,21). We have recently characterized the expression and regulation of PEDF in human and rodent premenopausal endometrium, indicating that PEDF is dynamically expressed in mice endometrium throughout the estrous cycle, in reciprocity to VEGF, and that the balance between the two is regulated by estrogen and progestrone (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that PEDF level declines with age, and suggested that this decline may play a key role in the development of angiogenic-related pathologies (18). Moreover, it was shown that decrease in PEDF expression is one of the mechanisms that promote tumor growth (19), suggesting PEDF as an anticancer therapy (20,21). We have recently characterized the expression and regulation of PEDF in human and rodent premenopausal endometrium, indicating that PEDF is dynamically expressed in mice endometrium throughout the estrous cycle, in reciprocity to VEGF, and that the balance between the two is regulated by estrogen and progestrone (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…The reason might be that the PEDF which successfully expressed in the tumor tissue increased the levels of p53 and BAX and concomitantly inhibited BCL-2. 7 This observation indicated that the growth inhibitory effect of C26 tumors was also associated with the apoptosis of C26 cells in vivo. Considering these results, D-NPs could successfully delivery PEDF gene into the tumor cells and would be a promising approach for antitumor therapy.…”
mentioning
confidence: 75%
“…[2][3][4][5] Pigment epithelium-derived factor (PEDF), as a member of the serine protease inhibitor (serpin) superfamily, has been reported to be one of the most potent inhibitors of angiogenesis. [6][7][8] PEDF is a 50 kDa secreted glycoprotein that belongs to a group of proteins having a common three-dimensional structure. 7 Compared with the direct protein administration, PEDF gene might be cheaper and achieve higher antitumor efficacy due to easier access to tumor tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEDF has numerous biological functions, including differentiating activity, neurite outgrowth, survival activity, anti-apoptosis and anti-angiogenic activities and the induction of cell death (13)(14)(15)(16)(17)(18)(19). The anticancer role of PEDF has yet to be elucidated; however, previous studies have suggested various roles for PEDF in inhibiting cancer progression.…”
Section: Introductionmentioning
confidence: 99%